Monitoring bioadhesion and biofim formation within biopits in archaeological potsherds by microscopic techniques - Soto, Daiana Marilé (2020)
Fil: Soto, Daiana Marilé. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología. Laboratorio de Arqueometría; Argentina.